Dividend Decision and Economic Value Added of Quoted Nigeria Manufacturing Firms - Michael, Agilebu Ogechi (American Economic & Social Review, 2019)
This study examined the effect dividend decision and economic value added of quoted manufacturing firms in Nigeria. The objective is to examine if dividend decision have any effect on economic valued added of the Nigeria firms. Cross sectional data was sourced from financial statement of 15 quoted manufacturing firms. Economic valued added was proxy for dependent variables while dividend yield, dividend payout ratio, retention ratio and dividend per share were proxy for predictor variables. After cross examination of the validity of the pooled effect, fixed effect and the random effect, the study accepts the fixed effect model. Findings revealed that75 percent variation from the fixed effect results on economic value added of the manufacturing firms. Beta coefficient of the predictor variables found that dividend yield have negative effect on economic value added while dividend per share, dividend payout ratio and retention ratio has positive and significant effect on economic value added of the quoted manufacturing firms. It’s therefore recommend that constant dividend decision should be maintained among the quoted manufacturing firms and retention forms should be properly invested and the investment environment should be well managed to increase economic value added through the dividend decision channel.